2007
DOI: 10.1016/j.socscimed.2007.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Job stress and poor sleep quality: Data from an American sample of full-time workers

Abstract: Given the associations between poor quality sleep and health, it is important to consider whether job stressors are related to sleep-related outcomes. Studies from Europe and Japan suggest that these stressors negatively impact sleep, but there are few studies of job stressors and sleep quality that draw upon large representative samples of workers in the USA. Using data collected via telephone interviews from a nationally representative random sample of 1,715 American full-time employees, this research consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
143
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(155 citation statements)
references
References 65 publications
8
143
1
3
Order By: Relevance
“…The decrease in sleepy driving, observed in the study population between 2001 and 2004, was likely to be facilitated by retirement during this period. The decreased likelihood of sleepy driving among those who retired is consistent with the findings of previous studies showing that job stress is associated with a poor quality of sleep (26) and that retirement provides additional time for night sleep and consequently decreases daytime napping (27). Likewise, the decrease in phone use while driving observed in the study population between 2001 and 2004 was facilitated by retirement, most likely because of the interruption of cell phone use for work purposes, which represents a large part of cell phone use during driving (28).…”
Section: Discussionsupporting
confidence: 90%
“…The decrease in sleepy driving, observed in the study population between 2001 and 2004, was likely to be facilitated by retirement during this period. The decreased likelihood of sleepy driving among those who retired is consistent with the findings of previous studies showing that job stress is associated with a poor quality of sleep (26) and that retirement provides additional time for night sleep and consequently decreases daytime napping (27). Likewise, the decrease in phone use while driving observed in the study population between 2001 and 2004 was facilitated by retirement, most likely because of the interruption of cell phone use for work purposes, which represents a large part of cell phone use during driving (28).…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, stress at work has been shown to be closely related to insomnia. In studies in other countries, the workload was positively related to stress, and negatively to autonomy in work 8) . In Japan a number of studies have surveyed the relation between workplace stress and insomnia.…”
Section: Introductionmentioning
confidence: 82%
“…The odds ratio for more than 6 h/day of VDT work compared to 6 h/day or less was higher for female participants than for males. The effect of being under high levels of stress, as defined by ERI and DCM, and widely used for theoretical occupational stress models as a risk factor for sleep disturbance, has been reported in many previous studies [14,33,36,[44][45][46][47][48]. It has been indicated that DCM is restricted to situational aspects of psychosocial work environment, whereas ERI has focused on salaries, promotion prospects, and job stability [49][50][51].…”
Section: Discussionmentioning
confidence: 99%